MENGHITUNG JUMLAH MOBIL DI AREA PARKIR BERBASIS MIKROKONTROLER ATMEGA8535 - Meyana, Vilia Eka (Just IT, 2011)
To know how many vehicles in parking area is needÃÂ  a machine that can work automatically. For that has been design and realized a conted system who can count many of vehicles based on microcontroller ATMega8535 complete with 4 sensor, infrared and the photodioda as a vehicle detector. The function of sensor 1 and sensor 2 is to calculating the number of vehicles which if the sensor is obstructed by the object and wait for sensor 2 obstructed too, and then the system will add the number of vehicles entered. The function of sensor 3 and sensor 4 is inversely with sensor 1 and sensor 2 that if sensor 3 and sensor 4 blocked by the object accordingly the system will reduce the number of vehicles that exit. Later on this system connected with microcontroller ATMega8535 and incoming data will be processed and displayed at seven segment and personal computer. Microcontroller as main controller is build to count the number of vehicles.